IMPROVING COMMUNITY AWARENESS ON PREVENTION OF COVID-19 TRANSMISSION THROUGH SHARING EXPERIENCES BY NURSES AND SURVIVOR - Andri Setiya Wahyudi; Candra Panji Asmoro; Hakim Zulkarnain; Achmad Tirmidzi (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
The situation of the increasingly massive spread of Covid-19 in Indonesia has forced several countries to issue travel restrictions for their citizens entering Indonesia, as well as prohibiting Indonesian citizens from visiting their country. Health promotion is needed that can raise the awareness of Indonesian citizens to adhere to health protocols. This community service activity seeks to increase public awareness by sharing experiences from survivor and nurses of Covid-19 patients at community health services (CHS) and in field hospitals. Health promotion through webinars, which are open publicly and for free, took place on September 29, 2020. Webinars through the Zoom application and broadcast live streaming on Youtube media with the channel name